Analisis Kinerja dengan Pendekatan Balanced Scorecard pada The Coffee Bean and Tea Leaf - Begawan, Tansri Ayu (E-Jurnal Akuntansi, 2013)
ABSTRACT In a business organization, a company that is able to excel in competition to realize its vision and mission to achieve the company's goals is an achievement that can measure the success of the company in evaluating the results of activities carried out by the company compared to a predetermined benchmark. Balanced Scorecard is a measurement tool as a counterweight to the financial aspect and the non-financial aspects, such as customer satisfaction, internal business processes, learning and growth within the company. Based on the analysis of performance appraisal in mind that The Coffee Bean and Tea Leaf Bali in the balanced scorecard as a whole is good. This is shown by the increase in revenue from 2010 to 2011. Actual costs were lower from 2010 to 2011 show The Coffee Bean and Tea Leaf Bali has done cost efficiency. In the customer perspective, customer satisfaction results show that customers are satisfied with the performance of The Coffee Bean and Tea Leaf Bali. Internal business process perspective shows good results seen from the company's complaint ratio. Then, the learning and growth perspective showed an increase in employee productivity and satisfaction of employees working at The Coffee Bean and Tea Leaf Bali.   Keywords: Balanced Scorecard, measurement tool